2008
DOI: 10.1111/j.1365-2958.2008.06306.x
|View full text |Cite
|
Sign up to set email alerts
|

A role for Lon protease in the control of the acid resistance genes of Escherichia coli

Abstract: SummaryLon protease is a major protease in cellular protein quality control, but also plays an important regulatory role by degrading various naturally unstable regulators. Here, we traced additional such regulators by identifying regulons with co-ordinately altered expression in a lon mutant by genome-wide transcriptional profiling. Besides many members of the RcsA regulon (which validates our approach as RcsA is a known Lon substrate), many genes of the s S -dependent general stress response were upregulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 61 publications
2
23
0
Order By: Relevance
“…20,29 In addition, GadW is under direct control of the PhoPQ two-component system, 30 and it has been shown that EvgAS can cross-talk to PhoPQ via the connector protein encoded by b1500 (also known as safA 26 ), which resides directly upstream of and in the same operon as YdeO. 18,31 As a first step to building a mathematical description of this complex network, we wished to assess whether a dynamic approach to monitoring gene expression within the network was both feasible and valid and in particular whether such an approach would reveal any novel aspects of the network that had not been detected to date.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…20,29 In addition, GadW is under direct control of the PhoPQ two-component system, 30 and it has been shown that EvgAS can cross-talk to PhoPQ via the connector protein encoded by b1500 (also known as safA 26 ), which resides directly upstream of and in the same operon as YdeO. 18,31 As a first step to building a mathematical description of this complex network, we wished to assess whether a dynamic approach to monitoring gene expression within the network was both feasible and valid and in particular whether such an approach would reveal any novel aspects of the network that had not been detected to date.…”
Section: Introductionmentioning
confidence: 97%
“…[15][16][17][18] In E. coli K-12, these effectors are subject to tight transcriptional control and are expressed at low levels during rapid growth at neutral pH, due in part to global H-NSmediated repression 15,19 and Lon-mediated degradation of the central activator protein GadE. 20 For induction of this latter set of genes, distinct regulatory networks operate depending on the inducing conditions, which include a shift to sublethal pH 21 and growth into stationary phase. 19,22 A drop from pH 7 to sub-lethal pH 5.5 induces a number of AR effectors via the two-component system EvgA/EvgS, which is encoded outside of the AFI.…”
Section: Introductionmentioning
confidence: 99%
“…We favor this possibility over transcriptional regulation of hsrA because previous efforts to manipulate gene expression through controllable promoters and gene duplication, while achieving increases in hsrA mRNA levels, did not result in changes in the protein level (38,60,65). Proteolytic degradation of transcription factors is considered a common mechanism involving proteases such as ClpX and Lon (66)(67)(68). In this regard, the expression level of the serine protease HtrA has been shown to increase upon exposure of H. pylori to hydrogen peroxide (69).…”
Section: Fig 10mentioning
confidence: 99%
“…In addition, many other genes which express metabolic enzymes, periplasmic proteins and regulators involved in AR in E. coli have also been examined by microarray and proteomic 2D-gel analyses (Blankenhorn et al, 1999;Tucker et al, 2002). Recently, the Lon protease, endoRNase RNase E and chaperone Hsp31 have been shown to be important in controlling AR systems in E. coli (Heuveling et al, 2008;Mujacic & Baneyx, 2007;Takada et al, 2007), and the roles of AraC-family regulators GadX and GadW and the multidrug resistance regulator MarA in AR systems have also been investigated (Ruiz et al, 2008;Sayed et al, 2007;Tramonti et al, 2006). Nevertheless, despite advances in unravelling some of the regulatory networks involved in AR systems (Foster, 2004;Masuda & Church, 2003), it remains unclear how these factors function together to promote cell survival in low pH conditions.…”
Section: Introductionmentioning
confidence: 99%